ANALISIS POTENSI SDM DALAM PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI DESA COGREG KECAMATAN PARUNG KABUPATEN BOGOR - Yasmin Fitriani; Rahmat Subur (Journal of Research and Publication Innovation, 2025)
This research aims to determine how the potential and quality of human resources affect the development and success of MSMEs in Cogreg Village, as well as determine the barriers or challenges faced by human resources in the development of MSMEs, such as lack of access to information, capital, or support from related institutions. This research method uses a descriptive qualitative method with SWOT analysis obtained through interviews and Forum Group Discussions (FGDs) with community representatives in Cogreg Village, Parung Sub-district, Bogor Regency. The results and discussion of this research show that the potential of human resources in Cogreg Village with the existence of local skills and knowledge can be utilized for the development of MSMEs. However, there are several obstacles such as limited technical training, limited capital, some MSME actors lack business legality and limited access to modern technology. In this study, the right strategy was obtained, namely implementing the Strenght - Opportunity (SO) strategy, namely making unique products that are in accordance with market preferences by utilizing the strengths of human resources and developing online platforms to sell MSME products and using advances in digital technology to reach a wider market. Weakness - Opportunity (WO) strategies, namely conducting training and providing access to modern technology to take advantage of digital market opportunities and seeking funding opportunities from government programs or microfinance institutions to overcome capital shortages and improve facilities.